Optimalisasi Produksi Bakso dengan Menggunakan Pendekatan Integer Linear Programming Pada Rumah Makan Jawa Lumintu - David Kapele; James Mangobi (Griya Journal of Mathematics Education and Application, 2026)
Micro, small, and medium enterprises (MSMEs) in the culinary sector often face production planning problems due to limited raw materials and production decisions based on estimation. This study aims to determine the optimal production quantities of several meatball variants at Rumah Makan Jawa Lumintu using Integer Linear Programming (ILP) assisted by POM-QM for Windows. This research is an applied quantitative study in Operations Research. Data were collected through observation and interviews regarding raw material composition, production output, inventory availability, and the production system. A mathematical model was developed to maximize total meatball production by considering raw material constraints, minimum production requirements, and integer restrictions. The results showed that the optimal production combination in a four-day production cycle consists of 5942 regular meatballs, 150 tenes meatballs, 200 tendon meatballs, and 50 super meatballs, yielding a maximum production of 6342 meatballs. Compared with the actual production of 5320 meatballs, the optimization model increased output by 1022 meatballs or 19,21%. Therefore, ILP assisted by POM-QM for Windows can be used as an effective tool for more optimal, efficient, measurable, and data-driven production planning.